FUNDAMENTALS OF MEDICINAL PLANT PRODUCTION TECHNOLOGY - Vahobova Feruzakhon Bakhtiyorjon qizi; Abdullajonova Nafisahon Ilhomjon qizi; Inomjonov Muhammadali Ilhomjon Ogli (Galaxy International Interdisciplinary Research Journal, 2022)
The role of medicinal plants in human life is unique. Medicinal plants have been used since ancient times. It is important to extract the necessary substances from medicinal plants. In this regard, the technology of collection and preparation of medicinal plants This article provides information on the basics of such technologies